Beginnings of inclusive education for people with intellectual disabilities in Chile. A Historical Perspective, 1928-1950 (2023)
Objective: to analyze the historical trajectory of intellectual disability in Chile in the period 1928-1950, starting with the educational reform that states that all citizens must be educated -regardless of their condition-, until the emergence of therapeutic pedagogy, which coincides with the end of the radical governments in Chile. Originality/Contribution: The research arises due to the scarce empirical evidence on the history of intellectual disability in Chile. In this context, research on the history of the education of children with intellectual disabilities is practically non-existent in Chile. Method: The methodology is qualitative and is based on an interpretative paradigm with a historiographic design. It uses a systematic bibliographic review of the normative on disability.  Strategies/information collection: Review and analysis of primary and secondary sources in three specific areas of study: 1) regulations on intellectual disability in Chile, 2) conceptualization of models of intellectual disability, and 3) historical milestones of disability in the period 1928 and 1950. Conclusions: The history of the education of people with intellectual disabilities in Chile in this period -based on the study of the regulations- has been permeated from its beginnings by a segregationist and discriminatory model that emerges from the policies, invades the semantics, and generates several constitutive milestones within the discipline of inclusive education, whose epistemological foundations require further study to be understood. The scientific techniques of the time identified, through biomedical parameters, a causal relationship between physical and cognitive underdevelopment.